Untangling mechanisms structuring insect diversity patterns in the Cape Floristic Region : the Restionaceae and their herbivores - Kemp, Jurene Ellen (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.